Management of Foreign Body of Peanuts in the Trachea in Children - Jerry Tobing (Buletin Farmatera, 2020)
Foreign body is an object that enters an organ that comes from outside the body or from inside the body that does not normally exist. One of the objects in the respiratory tract can occur in the trachea and occur in many children. Case report: a girl, 1 year 11 months of age with complaints of shortness of breath since 1 day before, had tachypnea, indirect laryngoscopy: multiple secretions, difficulty speaking vocal cords, inspiratory-expiratory stridor (+), suprasternal, epigastric and intercostal ( +). Bronchoscopy: white round foreign body (impression: peanut) covering> 50% of the tracheal lumen over the carina, mucosal edema, and hyperemia. A bronchoscopy was administered as a diagnostic and therapeutic role